Influence of laser power fluctuations on the quality of additive manufactured workpieces - Heinl, Martin; Galovskyi, Bogdan; Bayer, Florian; Laumer, Tobias; Hausotte, Tino (Lasers in Manufacturing (LiM), 2017)
There is a great potential in selective laser sintering (SLS) processes caused by increasing application areas in the field of additive manufacturing (AM). The related requirements to the quality of additive manufactured workpieces can be attributed to its process parameters. In this context, the examination of laser power fluctuations is interesting because of its direct influence on the workpiece quality. If the planar energy input into the powder bed is not constant, local areas can melt inhomogeneously beside the expected gauss-distributed intensity profile of the laser spot. For quality assessment a testing workpiece and its manufacturing strategy have been developed to measure the interactions between laser power and dimensional accuracy. Initially the appearing losses of the laser power in the beam path have been observed to optimize the energy input. In addition to the warm-up behaviour of the CO2-laser, appearing energy peaks during short-term sequences also show an influence on the workpiece quality. Finally in post-process quality assessment, the correlations of laser power with the dimensional accuracy and surface roughness are analysed by optical fringe projection and focus variation techniqu
Keywords: CO2-Laser; selective laser sintering (SLS); energy input; laser power fluctuation; dimensional deviation

In-Situ Contour Detection of Additive Manufactured Workpieces - Heinl, Martin; Karl Schmitt, Fabian; Hausotte, Tino (ScienceDirect - Procedia CIRP 74, 2018)
Due to the growing number of applications for additive manufacturing (AM) there is an increasing need for enhanced quality control methods. One approach is the in-situ analysis of manufactured workpiece contours layer by layer and the associated melting pool dimensions to ensure the conformity with the geometrical product specifications. For this purpose an accurate optical detection of the workpiece contour in combination with an alignment to the ideal layer model is needed. Considering a selective laser sintering (SLS) process, edge-detection algorithms have been compared and applied with improved settings. Image sets with varying illumination conditions of different directions are recorded and evaluated. In addition, the influences of the resulting shadows at the contour edges have been investigated. In this context filter methods are tested to further optimize the captured images for the detection process. Consequently an adapted in-situ measurement system is implemented to achieve the specific requirements of powder bed based additive manufacturing processes. <br
Keywords: Additive Manufacturing (AM); optical imaging; edge detection algorithms; geometrical product specification

Measuring procedures for surface evaluation of additively manufactured powder bed based polymer and metal parts - Heinl, Martin; Greiner, Sandra; Wudy, Katrin; Pobel, Christoph; Rasch, Michael; Huber, Florian; Papke, Thomas; Merklein, Marion; Schmidt, Michael; Körner, Carolin; Drummer, Dietmar; Hausotte, Tino (Measurement Science and Technology, 2020)
Powder bed-based additive manufacturing has become increasingly important for industrial applications. In the light of this, qualitative considerations such as the geometrical accuracy, the resulting mechanical properties, and the surface quality of additively manufactured parts must be taken into account. Optical measuring techniques such as confocal laser scanning microscopy, fringe projection and focus variation as well as profilometers are evaluated here, to determine the surface quality of powder bed-based manufactured parts. Even though these surface evaluation methods are established commercially, no standardized measuring procedure has yet been established. Within an experimental study the validity and accuracy of surface measurement methods are evaluated below, taking the limitations of each measurement system and the comparability of areal surface textures into account. The examinations are carried out with the powder materials EN-AW2024, Ti-6V-4Al and PA12, which are processed by electron beam melting, and laser beam melting of metals and polymers. Guidance for a consistent and comparable surface evaluation is thereby provided.
Keywords: Additive manufacturing (AM); laser beam melting (LBM); electron beam melting (EBM); guidance for consistent surface evaluation; comparison of optical and profilometer surface measurements

Methods and procedure of referenced in situ control of lateral contour displacements in additive manufacturing - Lerchen, Martin; Hornung, Jakob; Zou, Yu; Hausotte, Tino (Journal of Sensors and Sensor Systems, 2021)
Additive manufacturing technologies are further developing from prototype to serial production. This trend requires rising challenges to the process-accompanying quality assurance. Optical in situ quality control approaches show great potential to generate accurate measurement data, which are essential for feedback control. If a reliable referencing concept for the layer-by-layer measured data is guaranteed, contour information can be used during the manufacturing to correct occurring geometrical deviations. Within this scientific study, two methods of optical, referenced in situ control of lateral displacements of additive manufactured contours are presented. In the first approach the 2-D contour of the melting pool is analysed in relation to a position-stable reference system implemented in the powder bed. The second approach uses the translucent contour of deeper layers covered with powder as a reference. Within the image evaluation several pre-processing steps like calibration, undistortion, rectification, illumination correction and low-pass filtering are essential for reliable and correct geometric measurements. The following adapted contour detection and position determination of the referenced melting pool contours are based on an extended edge detection algorithm according to Canny (1986). With the evaluation of further manufacturing layers of already lowered powder bed levels, it is possible to specify the influence of powder application on geometrical displacements separately. This is done by a comparison of the position of the detected powder-covered melting pool contours with the previously applied melted region. Consequently a better understanding of lateral contour displacements within the additive manufacturing process is the goal, which is important for a process-accompanying correction of geometrical deviations.<br
Keywords: Additive manufacturing (AM); optical in situ monitoring; image pre-processing; contour detection; referenced contour determination; lateral contour displacements

Numerical and experimental study of the powder bed characteristics in the recoated bed of the additive manufacturing process - Schiochet Nasato, Daniel; Heinl, Martin; Hausotte, Tino; Pöschel, Thorsten (PARTICLES, 2017)
Part of the optimization steps for additive manufacturing is related to the correct understanding of the mechanical behavior of the powder used in the process. Obtain this understanding based purely on experiments might be a difficult and sometimes prohibitive task. A particle-based numerical tool can provide critical information for correct understanding of powder deposition process. Numerical simulations through the Discrete Element Method (DEM) provide a useful mean to investigate the additive manufacturing process, given the possibility to study particle-scale information that are difficult to access experimentally. The characteristics of the recoated powder bed are investigated in the packed bed region and onto the manufactured part using PA12 commercial powder. Particle size distribution, contact and non-contact cohesive forces are incorporated in the numerical model. Furthermore, the non-spherical shape of real particles is taken explicitly into account in numerical simulations. A blade-type recoating system is used to form the powder bed and its roughness is calculated. Experimental measurements are performed by fringe projection. Several areas of the recoated powder layers can be scanned with this optical measurement method. Thus, the analyzed surface roughness can be compared with the simulated quantities to validate the numerical model. The sintered part is modelled as a prescribed rigid static region in the simulated system. The powder recoated in the sintered region may have different characteristics (packing, roughness) compared to the powder bed region. Recoating process is modelled using two different shapes for the sintered region. The amount of material recoated and the surface roughness are then calculated for the powder bed as well as for the sintered regi
Keywords: Granular Materials; DEM; Additive Manufacturing; Surface Roughness; Numerical simulation

Referencing of powder bed for in situ detection of lateral layer displacements in additive manufacturing - Lerchen, Martin; Schinn, Julien; Hausotte, Tino (Journal of Sensors and Sensor Systems, 2021)
An increasing number of additive manufacturing (AM) applications leads to rising challenges for the processaccompanying quality assurance. Beside post-processing measurement systems, in situ monitoring systems in particular are currently requested to ensure feedback controlling during AM processes. For data acquisition and subsequent evaluation a high data quality is of importance. It depends on a high resolution and accuracy of measurement systems, adapted measurement conditions and a reference to the powder bed or component for geometric measurements. Within this scientific study, a new reference system has been implemented into the powder bed to reduce measurement deviations by an abbreviated metrological loop. After data acquisition and image processing layer by layer, the position stability of the reference system has been analysed in relation to the optical measuring system. Based on a contour detection of the reference markers, the evaluation of geometrical process deviations is presented as an essential basis for a closed-loop controlling system. Thermally induced and mechanical drifts within the manufacturing process can be verified by the reference system in the powder bed. As an outlook two methods are suggested for a process-accompanying referenced detection of the melting pool and resulting contour displacements during additive manufacturing.<br
Projekt ID 61375930 - Teilprojekt C4
Keywords: Additive manufacturing (AM); laser beam melting (LBM); reference system; metrological circuit; optical in situ monitoring; lateral displacements

Surface and dimensional measurements of additive manufactured workpieces - Heinl, Martin; Galovskyi, Bogdan; Hausotte, Tino (Proceedings of 6th International Conference on Additive Technologies, 2016)
Application areas of additive manufacturing (AM) have increased during recent years. Within the framework of AM, the selective laser melting (SLM) of raw powder materials is one of the most frequently used methods. This near net shape process allows simultaneous manufacturing of many workpieces and demands to high quality requirements. There is a wide potential of improvements relating to the process and its parameters, based on specific quality values. The current work is aimed to evaluate the quality of SLM workpieces from the manufacturing metrology point of view. Dimensional and surface parameters of the manufactured test workpieces are investigated by tactile and optical measurement approaches. In this context a socalled test artifact is developed, which enables the inspection of different geometrical features deviations and surface characteristics. Thus a better knowledge about the compatibility of measurement techniques could be achieve
Keywords: additive manufacturing; test artifact; tactile profil measurement; focus variation; fringe projection

Temperature-dependent optical material properties of polymer powders regarding in-situ measurement techniques in additive manufacturing - Heinl, Martin; Laumer, Tobias; Bayer, Florian; Hausotte, Tino (Polymer Testing, 2018)
Due to the growing number of applications for Additive Manufacturing (AM), an increasing need for enhanced quality control methods exists. Here optical measurement techniques are often used for in-situ monitoring in AM. There is a great potential to standardize and improve applications of optical measurement devices in accordance to the increasing requirements of measuring tasks. Beside the optical material qualifications, especially process-oriented changes in optical effects are of great relevance for in-situ evaluations. The optical modifications may be attributed to aggregate specific phase transitions coming along with variable emitted wavelengths. A measuring setup with two integrations spheres and a heated process chamber have been developed to analyze the optical interactions of laser radiation and visual illumination with the powder. The process oriented analysis for selective laser sintering lead to improved operating conditions in the field of in-situ measurements in combination with an accurate evaluation of the absorption ratio of the examined powde
Keywords: Additive Manufacturing; Selective Laser Sintering; In-Situ Measurement; Process-Oriented Optical Material Qualifica-tion; Integration Spheres

Vereinfachte Qualitätsbeurteilung in jeder Raumrichtung Additive Manufacturing - Qualitätssicherung additiv gefertigter Bauteile anhand von Test-Artefakten - Heinl, Martin; Loderer, Andreas; Galovskyi, Bogdan; Hausotte, Tino (wt Werkstattstechnik - Online, 2016)
Additive Fertigungsverfahren, wie das selektive Laserstrahlschmelzen entwickeln sich immer mehr zu etablierten industriellen Herstellprozessen, die eine schnelle und endkonturnahe Fertigung von Bauteilen variierender Komplexität ermöglichen [1]. Damit einher geht ein anhaltender Trend zu individuellen und qualitativ hochwertigen Produkten, was zu erhöhten Qualitätsanforderungen führt. Um diesen Ansprüchen gerecht werden zu können, werden seitens der Fertigungsmesstechnik geeignete Methoden für die Qualitätsanalyse entwickelt. Eine Post-Prozess-Qualitätskontrolle soll dabei eine langfristige Evaluierung der Maschinen- und Prozessfähigkeit und eine direkte Vergleichbarkeit unterschiedlicher Fertigungsprozesse gewährleisten. Der Schwerpunkt der Qualitätsbeurteilung liegt verstärkt auf der messtechnischen Erfassbarkeit und Analyse spezifischer Merkmale an Testbauteilen. Diese sogenannten Artefakte, die auf J.P. Kruth zurückgehen, ermöglichen eine Verifikation der Leistungsfähigkeit der Prozesse und zeigen daneben auch Fertigungsbegrenzungen auf [2]. In diesem Beitrag soll die Entwicklung einer standardisierten Prüfkette mittels Testbauteilen zur Post-Prozess-Qualitätsbeurteilung additiv gefertigter Bauteile beleuchtet werden. Hierbei steht zunächst die Charakterisierung einer geeigneten Referenzgeometrie im Vordergrund, die eine umfassende aber schnelle Qualitätsbeurteilung, bei gleichzeitig niedrigen Materialkosten, verbunden mit einem möglichst geringen Messaufwand vereinbaren soll [3]. Die Verifikation des qualitativen und quantitativen Benefits für die Fertigungsmesstechnik erfolgt am Beispiel einer Analyse der geometrischen Antastabweichungen der unterschiedlich komplexen Testbauteil
Keywords: Additive Fertigung; Fertigungsmesstechnik; Qualitätssicherung